THE MODERATING ROLE OF MANAGERIAL OVERCONFIDENCE IN THE NEXUS OF MANAGERIAL ABILITY AND FIRMS LEVERAGE - Aang Kunaifi; Sri Yayu Ninglasari; Santy Dwi Cempaka; Muhammad Saiful Hakim (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study aimed to investigate the impact of managerial ability on corporate financial leverage and examine the moderating role of managerial overconfidence in Indonesian publicly listed firms. The analysis was based on 1,440 firm-year observations from 2017 to 2020 and used fixed-effects regression models with firm clustered standard errors. The results showed that higher managerial ability was positively associated with greater financial leverage. Furthermore, it was found that managerial overconfidence increased this effect, suggesting that highly capable yet overconfident managers were more inclined to increase debt levels, potentially due to greater risk tolerance. This study contributed to the corporate finance literature by showing how cognitive biases interacted with managerial competence to influence leverage decisions, an interaction largely overlooked in traditional capital structure theories. These results offered practical implications for corporate governance, emphasizing the importance of complementing evaluations of managerial ability with behavioral assessments to minimize excessive risk-taking. In the context of emerging markets, this study emphasized the need for institutional reforms that consider both managerial skills and psychological traits in executive decision-making.